(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
To maintain or restore formation pressure by injecting gas or air into the formation, oil-saturated formations with steep flanks, good permeability, homogeneous rock composition and low viscosity are the most suitable objects.